Analysis of Kinetic Positional Solution and Workspace of Pure Translational 3-UPU Parallel Mechanism based on Matlab - Zhiqiang Zhu; Yanhong Xiong (Jixie chuandong)
The configuration and pure translational performance of 3-UPU parallel mechanism is analyzed by using spatial mechanism screw theory. The continuous polynomial algebraic topology method is proposed， the positive kinetic non-linear equations of 3-UPU parallel mechanism is built， and the solution of the equation set is calculated. By this approach， the solution of nonlinear kinetic equations of parallel mechanism can be found effectively without giving initial values. Meanwhile， the problems of divarication and divergence are also eliminated in the solving process， which have vital reference significance to the nonlinear transcendence problem solving. Based on Matlab/ Simmechanics， the kinetic PID control model of 3-UPU parallel mechanism is built and its workspace is analyzed to verify the accuracy in the application of spiral theory on parallel mechanism configuration design. This method provides feasible and practical reference significance to solve and analyze the kinematics problem of multiple degrees of freedom parallel mechanism.